2011
DOI: 10.1017/s1368980011000681
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in socio-economic differences in food habits over time

Abstract: Objective: To examine absolute socio-economic differences in food habits and their changes over time. Design: A longitudinal study using the cohort baseline mail surveys conducted in 2000-2002 (n 8960, response rate 67 %) and the follow-up in 2007 (n 7332, response rate 83 %), including data on seven food habits recommended in the national dietary guidelines, as well as socio-economic and sociodemographic variables. Setting: Data from the Helsinki Health Study survey, followed up for 5-7 years. Subjects: Munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
3
12
1
Order By: Relevance
“…This is in line with earlier studies (28, 30) but indicates a difference in bread consumption compared with Finland, where whole-grain rye bread is related to lower occupational class (19). A higher chance of eating more bread in total can be related to bread being relatively cheap and not needing any preparation if it is commercially baked.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with earlier studies (28, 30) but indicates a difference in bread consumption compared with Finland, where whole-grain rye bread is related to lower occupational class (19). A higher chance of eating more bread in total can be related to bread being relatively cheap and not needing any preparation if it is commercially baked.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, studies regarding consumers of different types of bread, the total intake, and the context of bread consumption have not previously been performed in a national representative setting in Sweden. Studies from Finland, however, have shown that a higher intake of rye bread was associated with lower occupational social class (19). Both white and rye bread consumption were associated with a lower educational level.…”
mentioning
confidence: 99%
“…Similar measurements of food habits have been used in previous studies (HelldĂĄn et al. , 2011; Seiluri et al. , 2011).…”
Section: Methodsmentioning
confidence: 76%
“…Furthermore, economic and cultural circumstances in society may particularly favour weight control behaviours among those in higher socioeconomic positions [20]. In our earlier study, those with higher occupational class were more physically active [21], and their food habits better followed the national guidelines [22]. This can contribute to socioeconomic differences in weight gain.…”
Section: Discussionmentioning
confidence: 99%